2022
DOI: 10.1073/pnas.2210857119
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanisms of ion adsorption to aqueous interfaces: air-water vs. oil-water

Abstract: The adsorption of ions to water-hydrophobe interfaces influences a wide range of phenomena, including chemical reaction rates, ion transport across biological membranes, and electrochemical and many catalytic processes; hence, developing a detailed understanding of the behavior of ions at water-hydrophobe interfaces is of central interest. Here, we characterize the adsorption of the chaotropic thiocyanate anion (SCN − ) to two prototypical liquid hydrophobic surfaces, water-toluene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…We hypothesize that different imidazolium cations form different structures at the interface, which consequently affect the entropic difference between the initial state and the transition state of CO 2 RR. Specifically, we suggest that 1 will form an ordered structure at the interface (low degree of disorganization, reaction controlled by entropic effects), while 2 will feature a more disordered structure, which is less able to stabilize the CO 2 reduction transition state. , Further evidence for our proposed mechanism comes from the observation that the symmetry factor β for species 1 decreases as the expected degree of ordering increases, supporting the notion that the initial state becomes more similar in nature to the transition state. ,, CO 2 reduction in the presence of 1 became temperature dependent for 40 °C and above, where more thermal energy is available to promote interfacial disordering, but more strongly so for low concentrations of 1 (Figure S3), reinforcing the idea that interfacial order controls the reaction outcome.…”
Section: Results and Discussionsupporting
confidence: 51%
“…We hypothesize that different imidazolium cations form different structures at the interface, which consequently affect the entropic difference between the initial state and the transition state of CO 2 RR. Specifically, we suggest that 1 will form an ordered structure at the interface (low degree of disorganization, reaction controlled by entropic effects), while 2 will feature a more disordered structure, which is less able to stabilize the CO 2 reduction transition state. , Further evidence for our proposed mechanism comes from the observation that the symmetry factor β for species 1 decreases as the expected degree of ordering increases, supporting the notion that the initial state becomes more similar in nature to the transition state. ,, CO 2 reduction in the presence of 1 became temperature dependent for 40 °C and above, where more thermal energy is available to promote interfacial disordering, but more strongly so for low concentrations of 1 (Figure S3), reinforcing the idea that interfacial order controls the reaction outcome.…”
Section: Results and Discussionsupporting
confidence: 51%
“…21 Theory and simulation work often compliment these experimental efforts; for instance, Benjamin and colleagues used molecular dynamic (MD) simulations to understand the structural and dynamical factors that influence ion transfer across L/L interfaces. 15,22 Furthermore, studies have discussed how L/L interfaces create ordered structures extending away from the interface. 23,24 For instance, Benjamin and Michael demonstrated that the time-dependent solvent response at the water/octanol interface is sensitive to the location of a newly formed charge and to the intrinsic width and structure of the interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, neutron reflectometry measurements have been paired with X-ray methods to provide missing insight into the light elements at the L/L interface . Nonlinear spectroscopies, such as vibrational sum frequency generation (SFG), have grown in recent years to enable measurements at oil/aqueous interfaces with surface specificity, chemical fidelity, and structural and orientational sensitivity. , For instance, we have employed SFG to understand ion paring and hydrogen-bonding interactions that drive the organization of ligand tail structures and aggregation at L/L interfaces away from equilibrium. These studies reveal interfacial speciation and kinetics of self-assembly that can be tuned by changing the aqueous subphase compositions, such as pH, supporting ionic species, or via the presence of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their fundamental importance, liquid/liquid interfaces are notoriously challenging to characterize both experimentally and within the analysis of modeling and simulation data. Although macroscopic properties like interfacial tension and surface potential are relatively easy to determine, several factors make a molecular-scale understanding of interfacial organization a challenge. The small length scale of the interfacial region (extending only a few molecular widths) limits the spectroscopic and scattering methods that provide chemical insight; the most prevalent are Vibrational Sum Frequency Generation (VSFG) or Second Harmonic Generation (SHG) and photoemission, while X-ray scattering and reflectivity methods have also been developed. Atomistic molecular dynamics (MD) simulations have played an incredibly important role in providing molecular-level details of the interfacial structure. For both simulation and experiment, the concentration gradients of solutes approaching the interface and their adsorption behavior, as well as their impact on interfacial properties such as reactivity and transport, have been a major area of study. …”
Section: Introductionmentioning
confidence: 99%